Characteristics and consequences of vortex wandering around a ship hull at drift: a numerical study. (1st July 2022) - Feder, Dag-Frederik; Shevchuk, Ivan; Sahab, Ahmed; Abdel-Maksoud, Moustafa
Abstract: The present paper investigates the major trailing vortex next to the KVLCC2 hull at 30°static drift and R e L o a ≈ 2 . 6 ⋅ 1 0 6 . Numerical simulations of a single-phase flow with the SST-based IDDES model are conducted with OpenFOAM. Proper orthogonal decomposition reveals the transverse displacement at the vortex centre. Spectral analysis indicates both the presence of a low-frequency broadband wandering motion and the existence of a distinct amount of turbulence at the centre by a broad inertial subrange. Tracking the instantaneous vortex centre in time reveals that the amplitude in relation to the core size is comparable to the far-field wingtip vortex studied by Devenport and colleagues in 1996. A new observation is the significant bending of the vortex axis. This reveals difficulties for the use of vortex planes being corrected for wandering. Following the correction is restricted to the vortex centre. One consequence of wandering is that about two thirds of resolved TKE can be attributed to it. Highlights: Hybrid RANS-LES prediction of vortex flow within near field wake. Wandering motion reveals distinct bending of vortex axis. About two thirds of TKE at vortex centre stem from wandering.